APPLICATION OF BLENDED LEARNING DURING THE COVID-19 PANDEMIC - Qalbi Shanaz Anandari; Urip Sulistyo; Afreni Hamidah; Sri Susanti (Jurnal Mantik, 2022)
This research was conducted State Elementary School 05/II Air Gemuruh in the even semester of the 2021/2022 academic year. This type of research is a qualitative research type of phenomenology. The subjects of this study were the principal and four teachers consisting of grade II, III, IV and V teachers. Data collection techniques used interview, observation and documentation techniques as well as data analysis techniques by collecting data, data reduction, data presentation and drawing conclusions. The results of the research are viewed from how the application of blended learning, preparation and implementation, mastery of technology, facilities and infrastructure, difficulties and efforts and evaluation. The application of blended learning at SD Negeri 05/II Air Gemuruh has met the requirements according to the health protocol.